Submission by the Food and Agriculture Organization of the United Nations (FAO) and the Consultative Group on International Agricultural Research (CGIAR) to the United Nations Framework Convention on Climate Change in relation to the topic of the Fourth Dialogue under the United Arab Emirates Just Transition Work Programme - Food and Agriculture Organization of the United Nations; Consultative Group on International Agricultural Research (Food and Agriculture Organization of the United Nations, 2025)
CGIAR, alongside partner FAO, completed a joint submission to the fourth dialogue of the Just Transition Work Programme, highlighting that a just transition is not possible without considering food systems and offering opportunities and actionable solutions for consideration.